The Impact of Changes in Short-Term Liabilities on the Share Price of PT XL Smart Tbk - Darmawan, Lauwrencia; Rachel Nur Ruhama Simatupang; Elizabeth Tiur Manurung (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study investigates the influence of short-term liabilities on the stock price of PT XL Smart Tbk over the period 2018–2025 using a simple linear regression framework based on 29 quarterly observations. Short-term liabilities are employed as the independent variable to assess the extent to which fluctuations in the company’s immediate financial obligations shape variations in its stock price. The regression results indicate a coefficient of –0.000309142, suggesting that an increase in short-term liabilities is associated with a decrease in stock price. However, the corresponding p-value of 0.117562308 demonstrates that this relationship is not statistically significant at the 5% significance level. The ANOVA output supports this finding, with a Significance F value of 0.117562308, indicating that the regression model does not provide sufficient explanatory power to establish a statistically meaningful relationship between the variables. The coefficient of determination (R Square = 0.0882633718) shows that only 8.83% of the variation in PT XL Smart Tbk’s stock price during 2018–2025 can be explained by short-term liabilities, while the remaining variation is influenced by macroeconomic conditions, sectoral dynamics within the telecommunications industry, market sentiment, and the firm’s operational performance. Although the effect is not statistically significant, the negative coefficient retains theoretical relevance within capital structure theories—particularly the Trade-Off Theory, Pecking Order Theory, and Signaling Theory—which posit that higher short-term financial obligations may elevate liquidity risk and potentially transmit adverse signals to investors.